Indications for and outcomes of therapeutic plasma exchange after cardiac transplantation: A single center retrospective study. Issue 4 (10th March 2018) - Onwuemene, Oluwatoyosi A.; Grambow, Steven C.; Patel, Chetan B.; Mentz, Robert J.; Milano, Carmelo A.; Rogers, Joseph G.; Metjian, Ara D.; Arepally, Gowthami M.; Ortel, Thomas L.
Abstract : Introduction: Limited data are available describing indications for and outcomes of therapeutic plasma exchange (TPE) in cardiac transplantation. Methods: In a retrospective study of patients who underwent cardiac transplantation at Duke University Medical Center from 2010 to 2014, we reviewed 3 TPE treatment patterns: a Single TPE procedure within 24 h of transplant; Multiple TPE procedures initiated within 24 h of transplant; and 1 or more TPE procedures beginning >24 h post‐transplant. Primary and secondary outcomes were overall survival (OS) and TPE survival (TS), respectively. Results: Of 313 patients meeting study criteria, 109 (35%) underwent TPE. TPE was initiated in 82 patients within 24 h, 40 (37%) receiving a single procedure (Single TPE), and 42 (38%) multiple procedures (Multiple TPE). Twenty‐seven (25%) began TPE >24 h after transplant (Delayed TPE). The most common TPE indication was elevated/positive panel reactive or human leukocyte antigen antibodies (32%). With a median follow‐up of 49 months, the non‐TPE treated and Single TPE cohorts had similar OS (HR 1.08 [CI, 0.54, 2.14], P  = .84), while the Multiple and Delayed TPE cohorts had worse OS (HR 2.62 [CI, 1.53, 4.49] and HR 1.98 [CI, 1.02, 3.83], respectively). The Multiple and Delayed TPE cohorts also had worse TS (HR 2.59 [CI, 1.31, 5.14] and HR 3.18 [CI, 1.56, 6.50], respectively). Infection rates did not differ between groups but was independently associated with OS (HR 2.31 [CI, 1.50, 3.54]). Conclusions: TPE is an important therapeutic modality in cardiac transplant patients. Prospective studies are needed to better define TPE's different roles in this patient population.